Pre and postharvest management of aflatoxin contamination in peanuts - Waliyar, Farid; Kumar, L.; Traoré, A.; Ntare, B.R.; Diarra, B.; Kodio, O. (CAB International, 2008)
Aflatoxins produced by Aspergillus flavus and Aspergillus parasiticus are common contaminants of peanut (Arachis hypogea) and a major threat to consumers, particularly in Sub-Saharan Africa. Aflatoxin contamination is a serious concern given their hepatotoxic properties and their widespread occurrence during cultivation, harvest, drying, storage, transit and distribution. Preharvest infection by A. flavus is the major cause of aflatoxin contamination in peanut. Its prevention is a complicated task that requires a series of intervention strategies to be merged with traditional farming practices. The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and its partners have developed an integrated approach to mitigate A. flavus infestation and aflatoxin contamination by combining: (i) host plant resistance, (ii) soil amendments with lime and organic supplements to enhance water holding capacity, plant vigor and seed health, (iii) timely harvesting and postharvest drying methods, (iv) the use of antagonistic biocontrol agents, such as Trichoderma and Pseudomonads, and (v) awareness campaigns and training courses to disseminate technology to the end-users. This approach can successfully reduce aflatoxin contamination in peanuts in West and Central Africa. This approach is simple, economical and suitable for subsistence farming conditions, but also can be scaled up for use on commercial farms in developing countries in Africa and Asia.